On the determinants of Airbnb location and its spatial distribution. Issue 8 (December 2019) - Eugenio-Martin, Juan L; Cazorla-Artiles, José M; González-Martel, Christian
This article explores Airbnb accommodation spatial distribution and it estimates the main determinants of its location choice. It employs spatial bivariate correlations and spatial econometrics to understand the heterogeneous spatial relationship between established hotels and Airbnb for three kinds of local tourism destinations: sun and beach, nature-based, and city. The case study concerns the Canary Islands where a good mixture of these attractions can be found. The main conclusion drawn is that Airbnb regulation needs to distinguish the kind of tourism. More precisely, Airbnb supply overlaps established hotels in city tourism, but it does not so clearly in sun and beach nor nature-based destinations. Airbnb supply matches tourist visits spatial distribution better than established hotels in city and nature-based destinations, but not in sun and beach destinations, where the incumbent hotels are closer to the tourism resources. Finally, the results from the spatial econometrics model shows that population size and the number of tourist visits matters as determinants of Airbnb location. However, the main determinant is price, which has got a much larger elasticity.